Bibliometric-Based Research Trends in Public Sector Accounting - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study aims to map and analyze the development of scientific literature on public sector accounting through a bibliometric approach. Using data extracted from the Scopus database and analyzed with VOSviewer, this research explores keyword co-occurrence, temporal evolution of research themes, density patterns, and collaboration networks among authors, institutions, and countries. The results indicate that public sector accounting research is strongly rooted in themes of accountability, transparency, new public management, and financial governance, which form the core intellectual structure of the field. Over time, however, the literature has expanded toward interdisciplinary topics such as sustainable development, climate change, public policy, and socio-economic analysis, reflecting a broader shift toward sustainability-oriented governance. Collaboration analysis reveals that scholarly production is dominated by European and North American institutions, although contributions from emerging economies are increasing, signaling a more globalized research landscape. Overall, the findings highlight the evolution of public sector accounting from a traditional administrative focus to a strategic framework supporting environmental accountability, policy evaluation, and public value creation. This study contributes by providing a comprehensive overview of research trends and identifying future directions, particularly the integration of sustainability and digital transformation within public sector accounting practices.